Using aequorin probes to measure Ca2+ in intracellular organelles. (June 2017) - Alonso, María Teresa; Rodríguez-Prados, Macarena; Navas-Navarro, Paloma; Rojo-Ruiz, Jonathan; García-Sancho, Javier
Graphical abstract: Highlights: Aequorins are valuable orthogonal tools for measuring Ca 2+ levels in organelles. GFP-aequorin fusions can be used both as luminescent and as fluorescent probes. Transgenic animals show normal phenotype and can be used for in vivo Ca 2+ monitoring. Abstract: Aequorins are excellent tools for measuring intra-organellar Ca 2+ and assessing its role in physiological and pathological functions. Here we review targeting strategies to express aequorins in various organelles. We address critical topics such as probe affinity tuning as well as normalization and calibration of the signal. We also focus on bioluminescent Ca 2+ imaging in nucleus or mitochondria of living cells. Finally, recent advances with a new chimeric GFP-aequorin protein (GAP), which can be used either as luminescent or fluorescent Ca 2+ probe, are presented. GAP is robustly expressed in transgenic flies and mice, where it has proven to be a suitable Ca 2+ indicator for monitoring physiological Ca 2+ signaling ex vivo and in vivo .